Entrepreneurial optimism, credit availability, and cost of financing: Evidence from U.S. small businesses - Dai, Na; Ivanov, Vladimir; Cole, Rebel A. (Journal of Corporate Finance, 2017)
Using a large sample of U.S. small businesses and a new measure of optimism, we examine the role of entrepreneurial optimism in small business lending. We provide evidence that optimistic entrepreneurs are not rationed by lenders. Quite the opposite, our results suggest that they often have better credit accessibility and obtain lower cost of financing. Our results are robust to alternative measures of optimism and controls for private information between lenders and borrowers.